Pengaruh pendidikan kesehatan tentang gizi balita terhadap pengetahuan ibu - Desi Ari Madi Yanti; Eni Agustin (Holistik Jurnal Kesehatan, 2022)
Background: Nutritional problems are a major health problem in toddlers. Malnutrition in toddlers can hinder mental development, physical growth, and thinking skills. Nutritional disorders in toddlers can be influenced by various factors, one of which is the low knowledge of parents, especially mothers. Efforts that can be made to increase mothers’ knowledge about nutrition are to provide health education.Purpose: Known that there is an influence of health education about toddler nutrition on mothers' knowledge.Method: Quasi-experimental research with pretest-posttest control group design. The population is all mothers who have toddlers who are in Ambarawa Timur. The sampling technique used was consecutive sampling with a sample of 42 participants.Results: It is known that the average score of participants before being given health education was 69.43 and the average score of participants after being given health education was 75.71.Conclusion:  There was an effect of health education on toddler nutrition on mothers’ knowledge about toddler nutrition in the working area of the Ambarawa Health Center in 2021 with a p-value of 0.000.Suggestion: Health services to be able to provide periodic health education to the community, especially mothers regarding the fulfillment of nutrition in toddlers as the first step in preventing growth and development problems for toddlers.Keywords: Toddler; Nutrition; Health education; Knowledge.Pendahuluan: Masalah gizi merupakan masalah kesehaatan utama pada balita. Gizi kurang pada balita dapat menghambat perkembangan mental, pertumbuhan fisik serta kemampuan berfikir. Gangguan gizi pada balita dapat dipengaruhi berbagai faktor salah satunya adalah rendahnya pengetahuan orang tua terutama ibu. Upaya yang dapat dilakukan dalam meningkatkan pengetahuan ibu tentang gizi adalah dengan memberikan pendidikan kesehatan.Tujuan: Diketahui pengaruh pendidikan kesehatan tentang gizi balita terhadap pengetahuan ibu.Metode: Penelitian quasi eksperiment dengan rancangan pretest-postest control group. Populasinya semua ibu yang mempunyai balita yang berada di AmbarawaTimur. Tekhnik sampling yang digunakan adalah consecutive sampling dengan sampel sebanyak 42 partisipan.Hasil: Diketahui rata-rata skor partisipan sebelum diberikan pendidikan kesehatan adalah 69,43 dan rata-rata skor partisipan setelah diberikan pendidikan kesehatan adalah 75,71.Simpulan: Ada pengaruh pendidikan kesehatan tentang gizi balita terhadap pengetahuan ibu tentang gizi balita di wilayah kerja Puskesmas Ambarawa tahun 2021 dengan p-value yaitu 0.000.Saran: Pelayanan kesehatan untuk dapat memberikan pendidikan kesehatan secara berkala kepada masyarakat terutama ibu tentang pemenuhan nutrisi pada balita sebagai langkah awal dalam mencegah terjadinya masalah tumbuh kembang bagi balita.